A novel and extremely stable nanofluid based on iron oxide nanoparticles: Experimental investigations on the thermal performance. (1st December 2021) - Souza, R.R.; Faustino, Vera; Oliveira, J.D.; Gonçalves, Inês M.; Miranda, João M.; Moita, Ana S.; Moreira, A.L.N.; Teixeira, José C.F.; Bañobre-López, Manuel; Lima, Rui
Highlights: Development of a stable nanofluid based on iron oxide nanoparticles. Hydrothermal synthesis process for the production of stable nanofluids. Nanofluid with excellent colloidal stability and superior thermal properties. Nanofluid with great potential to improve the performance of several thermal systems. Abstract: The analysis of the thermal conductivity of nanofluids (NFs) is extremely important to better understand the heat transfer mechanisms involved in the performance and efficiency of several thermal devices. In this work, two different NFs were tested using distilled water (DI-Water) as the base fluid. The first was a traditional NF formed by Al2 O3 nanoparticles (NPs) and the second was a novel NF formed by polyacrylic acid (PAA)-coated iron oxide NPs (Fe3 O4 @PAA), obtained from a hydrothermal synthesis route. The experiments were carried out with different NPs volume fractions and compared with DI-Water. The main objective of this study was to evaluate the effect of the incorporation of NPs with different chemical compositions on both thermal conductivity and colloidal stability of NFs. Additionally, the heat transfer capacity of NFs in single-phase laminar flow through a circular glass tube, subjected to the same flow under constant heat flux, was evaluated. Results have revealed that the proposed Fe3 O4 @PAA NF showed an enhancement of the heat transfer coefficient and was extremely stable when compared with the Al2 O3 -based NF.